Scattering of electromagnetic waves by a traversable wormhole - B. Nasr Esfahani (Iranian Journal of Physics Research, 2005)
Replacing the wormhole geometry with an equivalent medium using the perturbation theory of scattering and the Born approximation, we have calculated the differential scattering cross section of electromagnetic waves by a traversable wormhole. It is shown that scattering at long wavelenghts can essentially distinguish wormhole from ordinary scattering object. Some of the zeros of the scattering cross section are determined which can be used for estimating the radius of the throat of wormholes. The known result that in this kind of scattering the linear polarization remains unchanged is verified here.